Challenges of Remote Learning During the COVID-19 Pandemic: Students’ Experiences in the Perspective of M. Buber’s I-Thou and I-It Interaction - Advilonienė, Živilė (Pedagogika, 2025)
The quarantine imposed by the COVID-19 pandemic has led to a global shift towards remote learning while maintaining the coherence, smoothness, and quality of the study process. Based on the retrospective experiences of students (N-61) studying at college and university (students’ reflections were analysed according to the orientation questions they were asked), the article provides an overview of the challenges experienced during the quarantine period in terms of remote learning through virtual contact. The study revealed several groups of challenges experienced by students: informational, technical, educational, psycho-emotional, health, and ethical, caused by socio-legal constraints. The challenges experienced by the students during the remote learning process are addressed through Buber’s perspective of I-Thou and I-It interaction. The results of the study revealed that for objective reasons, remote learning was primarily oriented towards the I-It model of interaction, focusing on the delivery of information to the students, the technical quality, or the lectures. In many cases, for objective or subjective reasons, video cameras were not used in remote lectures, which hindered the creation of an immediate interaction between the lecturer and the students, based on the model of the I-Thou dialogue. Nevertheless, remote learning during the COVID-19 pandemic allowed the development of Buber’s I-Thou interaction, which is based on immediate mutual engagement, assuming favourable conditions.